Characteristics of Suspesi with Different Level of Biduri Leaf Extract at a Temperature of 75C, Traditional Cheese from Nusa Tenggara Timur - Sulmiyati, Sulmiyati; Malelak, Gemini E. M. (Faculty of Animal Science, Universitas Gadjah Mada, 2024)
The characteristics of the cheese produced are influenced by many factors, including the characteristics of the coagulant used. The characteristics of biduri leaf extract influence the characteristics of the suspesi. The research aimed to analyze the physicochemical, microstructure, and organoleptic characteristics of suspesi using different levels of biduri leaf extract given at a temperature of 75°C. This experimental study used a Completely Randomized Design with five treatments and three replications. Treatment is provided in making suspesi by adding biduri leaf extract, L1 = 2%, L2= 2.5%, L3 = 3%, L4 = 3.5%, L5 = 4%. Each level of bidi leaf extract was added at a temperature of 75°C. The variables measured were coagulation time, curd production, whey percentage, pH of curd, lactic acid percentage, water content, protein, fat, carbohydrates, L*, a*, b* color measurements, hardness, tannin content, microstructure, and organoleptic characteristics. The results obtained were that the significant effect (P<0.05), where there is an increase in coagulation time, whey percentage, lactic acid percentage, and organoleptic characteristics at the hedonic quality aspect of color, taste, texture, hedonic/preference aspect of taste and texture. and there has been a decrease in curd production. Furthermore, did not show a significant effect (P>0.05) on the pH of curd, water, protein, fat, carbohydrates content, hedonic quality aspects of smell, hedonic aspect of color, smell, the color of L*, a*, b*, Wi, Yi, hardness, tannin content. The microstructure there was to bond loose between protein and fat molecules. The conclusion given biduri leaf extract at different levels added at a temperature of 75°C, the characteristics of suspesi in physicochemical characteristics, organoleptic, and the microstructure of suspesi had decreased in line with the increase in the level of biduri leaf extract. The best suspesi was at a level of giving biduri leaf extract at 2%.